2020
DOI: 10.3389/fmed.2020.577468
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of the COVID-19 Epidemic on Orthodontic Patients in China: An Analysis of Posts on Weibo

Abstract: Background: During the COVID-19 pandemic, many dental care services including orthodontic practice were suspended. Orthodontic patients turned to social media platforms to communicate, share experiences, and look for solutions. Our study aimed to investigate the attitudes and perspectives of orthodontic patients during the COVID-19 epidemic in China by analyzing orthodontics-related posts on Sina Weibo (a Chinese counterpart of Twitter).Materials and Methods: Potentially eligible posts on Sina Weibo platform w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 34 publications
0
12
0
Order By: Relevance
“…The pandemic caused changes in people’s moods until it was brought under control, and we could quickly learn about these changes through social media. Due to easy access to social networks such as Twitter, researchers can use these tools as sources of data on many topics, such as attitudes toward health-related issues [ 25 , 26 ]. Twitter analysis revealed an increase in the number of tweets mentioning the toothache during the most intense period of the COVID-19 pandemic (11 March 2020 and 30 June 2020) and the intensity of emotions of “fear” and “anger”.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The pandemic caused changes in people’s moods until it was brought under control, and we could quickly learn about these changes through social media. Due to easy access to social networks such as Twitter, researchers can use these tools as sources of data on many topics, such as attitudes toward health-related issues [ 25 , 26 ]. Twitter analysis revealed an increase in the number of tweets mentioning the toothache during the most intense period of the COVID-19 pandemic (11 March 2020 and 30 June 2020) and the intensity of emotions of “fear” and “anger”.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, 16.5%, 28.8%, and 8.1% of the participants reported moderate to severe depression, anxiety, and stress levels, respectively. In a recent study, it was argued that the COVID-19 pandemic affected orthodontic appointments and provoked patients’ anxiety and that the biggest concern of more than half of the patients was the delay in treatment [ 26 ]. The emotions felt about toothache during the pandemic were fear (80.3%), anger (11.7%), sadness (5.9%), and joy (2.1%), respectively.…”
Section: Discussionmentioning
confidence: 99%
“…These results show the necessity to propose standard guidelines for dental practice before the pandemic outbreak. A recent study from China [ 25 ] performed with 2699 orthodontists suggested that COVID-19-related training programs necessitate enhancing knowledge and preparedness. A recent study used the same questionnaire tool [ 24 ] found adequate knowledge and perceptions scores among dental specialists from various clinical specialties.…”
Section: Discussionmentioning
confidence: 99%
“…The authors also opined that adequate and suitable protection should also be provided to ensure safety and reduce the psychological burden. However, the results cannot be applied to the present study as the Chinese study [ 25 ] was conducted among the orthodontists.…”
Section: Discussionmentioning
confidence: 99%
“…The devices that have been shown to cause the maximum auditory damage are lowspeed and high-speed handpieces, ultrasonic cleaning instruments, high-velocity suction devices, and even model trimming machines [13]. As has been commonly seen during the last year, because of irregular lockdowns, many patients have been reporting to dental clinics with removed brackets, broken wires, and poor oral hygiene [14]. To fix removed orthodontic brackets and provide oral prophylaxis, many of the devices mentioned above are used, which has only added to the hazardous nature of our profession.…”
Section: Rise In Noise Levelsmentioning
confidence: 99%